Performance of Amazonian rubber tree clones in the plateau region of the State of São Paulo, Brazil - Gonçalves, Paulo de Souza; Bortoletto, Nelson; Sambugaro, Rosana; Furtado, Edson Luiz; Bataglia, Ondino Cleante; Ortolani, Altino Aldo; Júnior, Gentil Godoy (Pesquisa Agropecuaria Brasileira, 2001)
The objective of this paper was to evaluate, for a period of 10 years, the adaptability and phenotypic expression of superior characters of 10 clones of rubber tree (Hevea spp.) grown in the plateau of São Paulo State, Brazil. The clones in the field were arranged in a randomized block design with three replicates and six plants per linear plots. The results showed that the clone IAN 3156 recorded highest yield (65.57 g/tree/tap) followed by RO 45 (52.29 g/tree/tap), whereas the control clone RRIM 600 recorded 41.04 g/tree/tap over four years of tapping. All selected clones were vigorous, with girth range at opening varying from 37.01 cm (IAN 3193) to 49.41 cm (IAN 4493). The percentage range of plants able for opening were 30.0% for IAN 3703 to 93.75% for IAN 6323. Except for IAN 3156 with 7.0 mm and for IAN 4493 with 6.32 mm other clones had low thick virgin bark at open compared to the control clone RRIM 600, which recorded 6.18 mm. Concerned to wind damage, except for IAN 3193 all the studied clones experienced low incidence of wind damage. All clones showed low to very low incidence of tree dryness. A complementary evaluation of the best clones (IAN 3156, RO 45, Fx 3899 and IAN 4493) in different environment of the São Paulo State is suggested, to evaluate besides yielding other secondary characters with the purpose of future recommendation of planting material in large scale.